High-performance polymeric photovoltaic cells with a gold chloride-treated polyacrylonitrile hole extraction interlayer. (27th February 2018) - Jeong, Ji-Ho; Noh, Yong-Jin; Kim, Seok-Soon; Kwon, Sung-Nam; Na, Seok-In
Abstract: We introduce a high efficiency polymeric photovoltaic cell (PPV) to be obtained by polyacrylonitrile (PAN) hole extraction layer (HEL) modification with gold chloride (AuCl3 ). The role of PAN HELs with AuCl3 and their effects on solar cell performances were studied with ultraviolet photoemission spectroscopy, atomic force microscopy, internal resistances in PPVs, and current–voltage power curves. The resultant PPVs with AuCl3 -treated PAN HELs showed improved cell efficiency compared to PSCs with no interlayer and PAN without AuCl3 . Furthermore, with AuCl3 -treated PAN, we finally achieved a high efficiency of 6.91%, and a desirable PPV-stability in poly[[4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2-b:4, 5-b′]dithiophe-ne-2, 6-diyl][3-fluoro-2-[(2-thylhexyl)carbonyl]-thieno[3, 4-b]thiophenediyl]]:[6, 6] phenyl-C71 butyric acid methyl ester (PTB7:PC71 BM) solar cells, which is a comparable efficiency to the conventional devices with poly (3, 4-ethylenedioxythiophen):poly (styrene sulfonate) (PEDOT:PSS), but showing better PPV-stability than PEDOT:PSS.